Structure and neurotoxicity of novel amyloids derived from the BRI gene. (26th October 2005) - Gibson, G.; El-Agnaf, O.M.A.; Anwar, Z.; Sidera, C.; Isbister, A.; Austen, B.M.
Abstract : A number of human neurodegenerative diseases involve aggregated amyloid proteins in the brain, e.g. Alzheimer's disease (β-amyloid) and Parkinson's disease (α-synuclein). Other examples are rare familial dementias which involve the BRI gene. In a British family, mutation of the termination codon extends the reading frame of BRI to yield a furin-processed 34-residue peptide (Abri; British dementia peptide), 11 residues longer than the wild-type (WT). In a Danish family, a ten-base insertion also yields a 34-residue peptide (Adan; Danish dementia peptide). To explore the roles of Abri and Adan in neurodegeneration, we synthesized Abri and Adan in oxidized and reduced forms and generated transgenic mice colonies expressing the WT and mutated forms of BRI. We have generated transgenic mice colonies bearing the genes coding for WT-BRI, Adan and Abri under the control of the Thy1 promoter. Whereas WT-BRI transgenic mice express full-length WT-BRI protein in their brains, Adan protein is fully processed to small peptides.